1989
DOI: 10.1007/bf00438350
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific differences in fouling of two congeneric ascidians (Eudistoma olivaceum and E. capsulatum): is surface acidity an effective defense?

Abstract: Ascidian specimens were collected from the Indian River Lagoon, Florida, USA, in November 1987. Eudistoma olivaceum (Van Name) was fouled by only two species of epifaunal invertebrates and the percent cover of epibionts was negligible. Colonies of E. capsulatum (Van Name) were fouled by up to 17 species of epifaunal invertebrates, epibionts covered an average of 12.5% of the surface area of these colonies. Extracts of E. olivaceum exhibited potent cytotoxic, antimicrobial and antiviral activity in laboratory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…In contrast, the literature on tropical and temperate ascidians suggests secondary metabolite feeding deterrents are more common (Young & Bingham 1987, Lindquist & Fenical 1991, Lindquist et al 1992, Pisut & Pawlik 2002, López-Legentil et al 2006). The present study provides additional information relevant to the long-standing debate about the role of inorganic acids in the provision of defenses against predation in ascidians (Parry 1984, Davis & Wright 1989, Pawlik 1993, Pisut & Pawlik 2002. Stoecker (1978Stoecker ( , 1980 concluded that sulfuric acid in the tunics of Aplousobranch and Phlebobranch ascidians deterred potential predators and inhibited fouling.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In contrast, the literature on tropical and temperate ascidians suggests secondary metabolite feeding deterrents are more common (Young & Bingham 1987, Lindquist & Fenical 1991, Lindquist et al 1992, Pisut & Pawlik 2002, López-Legentil et al 2006). The present study provides additional information relevant to the long-standing debate about the role of inorganic acids in the provision of defenses against predation in ascidians (Parry 1984, Davis & Wright 1989, Pawlik 1993, Pisut & Pawlik 2002. Stoecker (1978Stoecker ( , 1980 concluded that sulfuric acid in the tunics of Aplousobranch and Phlebobranch ascidians deterred potential predators and inhibited fouling.…”
Section: Discussionmentioning
confidence: 73%
“…signifera that caused feeding deterrence in a suite of sympatric coral reef fish. Alkaloids (eudistomins) were also isolated from the tunic of the tropical colonial ascidian Eudistoma olivaceum (Davis & Wright 1989); these alkaloids did not deter fish feeding, but were effective as antifoulants (Davis 1991). Larvae of the Caribbean ascidian Trididemnum solidum contain a variety of secondary metabolites which deter feeding in the pinfish L. rhomboides, as well as in the sea urchin Arbacia punctulata and the sea anemone Aiptasia pallida.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These assays, however, did not decouple the possible defenses of acids from secondary metabolites that may decrease palatability. Heavy metals, such as vanadium, have also been proposed to provide ascidians with anti-predatory and anti-fouling defenses (Stoecker, 1978(Stoecker, , 1980a, but the validity of this hypothesis was subsequently disputed (Parry, 1984;Davis and Wright, 1989;reviewed in Pawlik, 1993;however, see Discussion).…”
Section: Introductionmentioning
confidence: 99%